PENGARUH PROFITABILITAS, LIKUIDITAS, SALES GROWTH, DAN ASSET TANGIBILITY TERHADAP STRUKTUR MODAL - Sherin Kusuma; Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The main purpose of this research is to show empirically the effect of profitability, liquidity, sales growth, and asset tangibility on capital structure of manufacturing companies listed on Indonesia Stock Exchange (IDX). The population of this study is from the year of 2019-2020 using 114 data consisted of 67 manufacturing companies that were selected using purposie sampling method. This research uses SPSS software version 18 to process the hypothesis. The result of the study showed that profitability, liquidity, andasset tangibility has negative and significant effect on capital structure, however there is no significant effect of sales growth on capital structure.